Goethe yearbook, Volume XXX publications of the Goethe Society of North America - Simpson, Patricia A. 1958-; Tautz, Birgit 1967-; Franzel, Sean 1976- (Camden House, 2023)
The Goethe Yearbook is a publication of the Goethe Society of North America, showcasing North American and international scholarship on Goethe and other authors and aspects of the late eighteenth and early nineteenth centuries. Volume 30 seeks to prompt discussion of new directions in eighteenth-century scholarship with special sections on Enlightenment legacies of race and on the robust scholarship that rethinks the eighteenth-century body beyond the human organism. Beyond the two special sections there are articles on Wieland's Alceste, several essays on sex and gender (e.g., on Goethe's Werther; on gender, genre, and authorship in La Roche and Goethe; and on continued gender bias in scholarship on the German eighteenth century), a co-authored article on Goethe's Roman elegies, and an article on performativity and gestures in Kleist. The customary book review section rounds out the volume